On the performance of online routing enabled translucent space division multiplexing-based elastic optical networks. (6th May 2020) - Iyer, Sridhar
We focus on lightpath optimisation in a space division multiplexing-based elastic optical network by proposing the online routing algorithm with regeneration algorithm which accounts for the presence of transceivers in the network, and also ensures routing of translucent lightpaths through spectral super-channels over spatial multiple core fibres links. In regard to regeneration, we investigate three different scenarios which differ in their regeneration variability level in addition to the adjustment of modulation formats according to the transmission route characteristics. We conduct extensive simulations considering two realistic network topologies and two different multiple core fibre crosstalk values which result in different transmission reach values. The obtained results demonstrate that the proposed algorithm significantly outperforms the various reference routing techniques, and significant benefits can be obtained in regard to the utilisation of resources with much lesser BwBP when regeneration is conducted with complete flexibility and modulation format conversion is permitted at every network node.